Lymphocytic hypophysitis causing hypopituitarism and diabetes insipidus, and associated with autoimmune thyroiditis, in a non-pregnant woman. - Paja, M. (BMJ Group, 1994)
A 25 year old non-pregnant woman presented with a one-year history of amenorrhoea and polyuria. Three months before her admission, she had suffered lymphocytic meningitis. Hormonal studies revealed hypopituitarism and central diabetes insipidus, with associated primary autoimmune hypothyroidism. Computed tomographic scan and magnetic resonance imaging showed a pituitary mass with suprasellar extension and thickened stalk. Transsphenoidal surgery was performed and the histological study revealed fibrosis and diffuse lymphocytic infiltration with predominance of CD4 lymphocytes. This further case of lymphocytic hypophysitis was not related to pregnancy and produced diabetes insipidus, two uncommon associations. We discuss the features that can lead to a preoperative suspicion of this rare disorder.